Karakteristik Minyak Atsiri Eucalyptus dari 3 Klon Pohon Eucalyptus pellita F. Muell - Riana Anggraini; Jauhar Khabibi; Rike Puspitasari Tamin (Jurnal Silva Tropika, 2019)
Essential oil is a non-timber forest product commodity that has a high selling value. PT. Wirakarya Sakti (PT. WKS) is one of the owners of an industrial plantation forest (HTI) that plants Eucalyptus pellita F. Muell. The utilization of this tree is only focused on wood for pulp production, so it produces leaf and bark waste. The E. pellita leaves are very potential to produce essential oils that have high selling value. However, the characteristics of essential oil from this E. pellita clones are still unknown. Therefore, it is necessary to analyze the quality of eucalyptus essential oils from these clones. The leaves of E. pellita from clone tree 77, 361, and 364 in PT. WKS was harvested and distilled using the water and steam distillation method to produce the essential oil. After that, the yield of essential, physical and chemical characteristics was analyzed following the Indonesian national standards (SNI 06-3954-2006). The results showed the yield percentage of eucalyptus oil from 3 clone trees are 0.080–0.130%. The results of physical and chemical characteristics of essential oil showed: (1) eucalyptus oil color is yellowish-green, (2) it has a distinctive smell of eucalyptus oil, (3) the specific gravity between 0.900–0.907, (4) 80% solubility in ethanol shows 1:10 turbid, (5) cineole percentage between 39.65–41.13%, and (6) refractive index between 1.462–1.463. The data analysis showed that clone 77 has a higher quality compared to the others.